Eutrophication and Deoxygenation Forcing of Marginal Marine Organic Carbon Burial During the PETM. Issue 3 (3rd March 2022) - Papadomanolaki, Nina M.; Sluijs, Appy; Slomp, Caroline P.
Abstract: The Paleocene‐Eocene Thermal Maximum (PETM) is recognized globally by a negative excursion in stable carbon isotope ratios (δ 13 C) in sedimentary records, termed the carbon isotope excursion (CIE). Based on the CIE, the cause, duration, and mechanisms of recovery of the event have been assessed. Here, we focus on the role of increased organic carbon burial on continental margins as a key driver of CO2 drawdown and global exogenic δ 13 C during the recovery phase. Using new and previously published sediment proxy data, we show evidence for widespread enhanced primary production, low oxygen waters, and high organic carbon (Corg ) burial in marginal and restricted environments throughout the δ 13 C excursion. With a new biogeochemical box model for deep and marginal environments, we show that increased phosphorus availability and water column stratification on continental margins can explain the increased Corg burial during the PETM. Deoxygenation and recycling of phosphorus relative to Corg were relatively mild, compared to modern day anoxic marine systems. Our model reproduces the conditions reconstructed by field data, resulting in a burial of 6, 000 Pg across the PETM, in excess of late Paleocene burial, and ∼3, 300 Pg C for the critical first 40 kyr of the recovery, primarily located on continental margins. This value is consistent with prior data and model estimates (∼2, 000–3, 000 Pg C). To reproduce global exogenic δ 13 C patterns, this Corg burial implies an injection of 5, 000–10, 000 Pg C during the first ∼100–150 kyr of the PETM, depending on the source's δ 13 C (−11‰ to −55‰). Key Points: Data and modeling show increased productivity, deoxygenation, and organic C burial in marginal and restricted environments during the PETM Excess burial of ∼3, 300 Pg organic C burial at the early stages of the PETM recovery Excess organic C burial during recovery requires several thousands of Pg of 13 C‐depleted carbon input to match global exogenic δ 13 C trends